Digital technologies make work more demanding - Lukowski, Felix [Verfasser]; Neuber-Pohl, Caroline [Verfasser] (My University, 2017)
"Although ongoing digitalisation of the production and of the service sector is stoking fears of job losses, there are indications that the overall effect on employment will be relatively slight. In fact, the main expectation is that the nature of work will fundamentally change. As the use of digital technologies increases, employees will be able to carry out more demanding tasks. This article uses data from a current additional survey of the BIBB Establishment Panel on Qualification and Competence Development to investigate the im-pacts of the deployment of digital technologies from firms’ point of view." (author's abstract ; BIBB-Doku)
Digitale Technologien machen die Arbeit anspruchsvoller
Keywords: G 2.2.1 Technologisierung; G 2.3 Wandel von Arbeit & Wirtschaft; G 2.3.4 Qualifikationswandel; Digitalisierung; Technisierung; BIBB-Qualifizierungspanel; Tätigkeitswandel; Qualifikationsanforderung; Zukunft der Arbeit